2009
DOI: 10.1017/s1049023x00007378
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Pandemic: A Perspective

Abstract: and your esteemed colleagues throughout the world who are working together to forge a new direction for this, the most exciting and humanitarian branch of health care. Be a part of the solution for the future of the world!

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Influenza A viruses have caused several pandemics during the last century, and continue to cause epidemics annually. The pandemic of 1918–1919 killed as many as 50 million people worldwide [4,5]. In 2009, a novel swine-origin influenza virus capable of rapid human transmission was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza A viruses have caused several pandemics during the last century, and continue to cause epidemics annually. The pandemic of 1918–1919 killed as many as 50 million people worldwide [4,5]. In 2009, a novel swine-origin influenza virus capable of rapid human transmission was reported.…”
Section: Introductionmentioning
confidence: 99%
“…12 This is particularly worrying if you consider the suggestion that ''a pandemic or an epidemic is not only how widespread a disease actually is, but rather how it is perceived.'' 30 Previous research showed that news media write about new infectious diseases in both a fear-inducing and reassuring way. The swine flu turned out to be more benign than a normal seasonal flu.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal flu kills an estimated 250,000-500,000 people worldwide every year, 29 yet this is not a topic that attracts much media attention. Looking back, “we learned that when there is a widespread perception of a major health risk for the community, minor incidents or major non-events can turn into a public health crisis.” 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation